Answer:
Option (B)
Explanation:
1). Given function is,
![f(x)=(1)/(x-1)+3](https://img.qammunity.org/2021/formulas/mathematics/high-school/x4traenxk7xtvetcfoapvr4irx3wty87pi.png)
It the given function 'f' is transformed by a translation of 2 units to the right, the new function will be,
h(x) = f(x - 2)
h(x) =
![(1)/((x-2)-1)+3](https://img.qammunity.org/2021/formulas/mathematics/high-school/q2pyfcgs226lvurr1kfgegb53irsx502g8.png)
=
![(1)/(x-3)+3](https://img.qammunity.org/2021/formulas/mathematics/high-school/n2gsrl6m4kn9k8i24jxgrvhy1e46j16gae.png)
Further the new function is translated by 6 units down,
g(x) = h(x) - 6
g(x) =
![(1)/(x-3)+3-6](https://img.qammunity.org/2021/formulas/mathematics/high-school/ouwg3mupksmt6ksjiu78yf7qx3o7q6ttg3.png)
=
![(1)/(x-3)-3](https://img.qammunity.org/2021/formulas/mathematics/high-school/15tzz230zpvxgzgxbzbxedf36krtf6jz55.png)
Since, transformed function 'g' passes through a point (x, -2),
g(x) =
![(1)/(x-3)-3](https://img.qammunity.org/2021/formulas/mathematics/high-school/15tzz230zpvxgzgxbzbxedf36krtf6jz55.png)
-2 =
3 - 2 =
![(1)/(x-3)](https://img.qammunity.org/2021/formulas/mathematics/college/yn6p0x0tnt9bifyyb3mwweybnmu8incxi0.png)
x - 3 = 1
x = 4
Therefore, Option (B) will be the answer.